Pengaruh Pemberian Kegel Exercise Terhadap Inkontinensia Urin Pada Lansia Di Posyandu Lansia Kenanga Dan Kanthil Di Desa Delanggu - Destianingrum, Wella; , Dwi Kurniawati, SSt.FT (2017)
Background: Urinary incontinence is the inability to hold urine. This situation can cause various medical problems, social, and economic. Urinary incontinence is more common to elderly women by a ratio of 2: 1 to UIA 80 years. Survey in Asian countries found that the prevalence of aryincontinence was 14.8% in women and 6.8% in menObjective: This study aimed to determine the effect of kegel exercises on urinary incontinence in the elderly in Posyandu Kenanga and Kanthil in the village Delanggu.Methods: This research method using quasi experiment. The study design used is non-randomized control group pretest posttest design. The samples using purposive sampling method that meets the criteria inklusi and exclusion. Total sample studies as many as 23 elderly. Results: The data were not normally distributed, statistical test to test the effect of using Wilxocon obtained value of p = 0.001 (<0.05). The statistical test for effect of using different test Mann Whitney obtained p = 0.000 (<0.05). Conclusion: Based on these data we can conclude that there is the effect of kegel exercise on urinary incontinence in the elderly.